2019
DOI: 10.1038/s41388-019-0763-0
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory cytokine IL-6 induces FRA1 deacetylation promoting colorectal cancer stem-like properties

Abstract: Colorectal cancer (CRC) has long been known for its tight association with chronic inflammation, thought to play a key role in tumor onset and malignant progression through the modulation of cancer stemness. However, the underlying molecular and cellular mechanisms are still largely elusive. Here we show that the IL-6/STAT3 inflammatory signaling axis induces the deacetylation of FRA1 at the Lys-116 residue located within its DNA-binding domain. The HDAC6 deacetylase underlies this key modification leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 49 publications
(63 reference statements)
0
40
0
1
Order By: Relevance
“…Interestingly, interference with those pathways by aspirin increased chemosensitivity and decreased self-renewal in breast cancer cells ( 531 ). In colorectal cancer cells the inflammatory cytokine IL-6 mediates deacetylation, which subsequently activates NANOG transcription and accumulation of stemness phenotypes, correlating with malignant progression and poor prognosis ( 543 ).…”
Section: The Escape Of Cancer Stem Cells From Therapymentioning
confidence: 99%
“…Interestingly, interference with those pathways by aspirin increased chemosensitivity and decreased self-renewal in breast cancer cells ( 531 ). In colorectal cancer cells the inflammatory cytokine IL-6 mediates deacetylation, which subsequently activates NANOG transcription and accumulation of stemness phenotypes, correlating with malignant progression and poor prognosis ( 543 ).…”
Section: The Escape Of Cancer Stem Cells From Therapymentioning
confidence: 99%
“…Aberrant genetic and epigenetic pro iles in numerous types of solid (prostate, breast, colorectal, lung) and haematological malignancies were found to be proportional with the level of their acetylated his-tones (Herceg and Hainaut, 2007). Histone deacetylation induced by the IL-6/STAT3 in lammatory signalling axis was shown to have a role in the transactivation of stemness factors in CRC (Wang et al, 2019). Also, it was found that the initiation, invasion and metastasis of gastrointestinal tumours were correlated with the global content of acetylated histones Chen and Fang (2015).…”
Section: %mentioning
confidence: 97%
“…IL-6 stimulates cancer growth, metastasis and immune evasion in several tumor types (36)(37)(38)(39)(40)(41)(42). Additionally, direct effects of IL-6 on cancer cells include an ability to promote stem cell characteristics (42)(43)(44)(45)(46), induction of mesenchymal traits (39) and resistance to therapies (47). IL-6 orchestrates the interactions between cancer cells and the TME by preparing the soil for cancer homing at target organs (36,48) and has been also shown to stimulate immune evasion by inducing the stabilization of programmed death-ligand 1 (PD-L1) (38).…”
Section: Il-6 and Il-1 Signaling In Covid-19 And Cancermentioning
confidence: 99%